Neurofibromatosis type 1, fibromuscular dysplasia, and ischemic stroke: an association lost in time? A case report - Fonseca, Igor Oliveira Da [UNESP]; Luvizutto, Gustavo José; Souza, Isaac Pantaleão [UNESP]; Trindade, André Petean [UNESP]; Freitas, Carlos Clayton Macedo De [UNESP]; Bazan, Rodrigo; Modolo, Gabriel Pinheiro [UNESP] (Sociedade Brasileira de Angiologia e de Cirurgia Vascular (SBACV), 2023)
Neurofibromatosis Type 1 (NF1) is a rare cause of ischemic stroke (IS) in the general population. We report a case of a young patient with NF1 in whom IS was caused by fibromuscular dysplasia. An angiographic study demonstrated occlusion in the right internal carotid artery (ICA), just after its origin, and the left ICA, just before the intracranial portion, and brain magnetic resonance imaging showed the limits of an area of brain infarction in the right frontoparietal region. Despite these concomitant neuroimaging findings, this association is rare, and it is difficult to establish the contribution to the outcome made by each of these diseases, which treatment is the best to implement, or what prognosis is.

A neurofibromatose tipo 1 (NF1) é uma causa rara de acidente vascular cerebral isquêmico (AVCi) na população geral. Neste estudo, relatamos o caso de um paciente jovem com AVCi, com diagnóstico de NF1 associada a displasia fibromuscular. O estudo angiográfico demonstrou oclusão da carótida interna direita, logo após sua origem, e esquerda, antes da porção intracraniana. A ressonância magnética do encéfalo mostrou delimitação de um infarto na região frontoparietal direita. Apesar desses achados concomitantes na neuroimagem, essa associação é rara, sendo difícil de estabelecer a contribuição de cada uma dessas doenças no desfecho, tampouco qual o melhor tratamento a ser implementado e qual o prognóstico.
Neurofibromatose tipo 1, displasia fibromuscular e acidente vascular cerebral isquêmico: uma associação perdida no tempo? Um relato de caso
Keywords: neurofibromatosis type 1; fibromuscular dysplasia; stroke; neurofibromatose tipo 1; displasia fibromuscular; acidente vascular encefálico